Contextualizing Hadith About LGBT in Perspective Humanity, Religion, and Culture - Waliko, Waliko (ILMU USHULUDDIN, 2023)
This article aims to contextualize LGBT-related hadiths from humanitarian, religious, and cultural perspectives. LGBT issues have become a complex debate in Indonesian society in recent years, especially as they are closely related to existing religious and cultural values. The purpose of this study is to analyze how LGBT-related hadiths are interpreted and applied in the Indonesian context, and how humanitarian, religious, and cultural perspectives play a role in this understanding. The study uses a qualitative approach by collecting and analyzing data from primary and secondary sources, including hadith texts, religious literature, and the opinions of religious and community leaders. The results of the analysis show that interpretations of hadith-reports on LGBT may vary depending on the religious, cultural, and humanitarian frameworks used. Some may use the hadith to oppose LGBT based on traditional interpretations, while others argue that humanitarian principles and social values should be prioritized. This study also examines the impact of contextualizing hadith about LGBT on religious, cultural and humanitarian views. It was found that the diversity of views in society on this issue reflects the conflict between religious values and the demands of a more inclusive humanity. This research illustrates the complexity of the context in interpreting and applying hadith traditions on LGBT in Indonesia. Differences between religious, cultural and humanitarian interpretations play an important role in shaping discussions and policies on this issue. Therefore, it is important to continue to promote inclusive dialogue and understanding in order to deal with LGBT issues wisely and with respect for different perspectives